Sirtuins and cognition: implications for learning and memory in neurological disorders - Fagerli, Eric; Escobar, Iris; Ferrier, Fernando J.; Jackson, Charles W.; Perez-Lao, Efrain J.; Perez-Pinzon, Miguel A. (Frontiers in Physiology, 2022)
Sirtuins are an evolutionarily conserved family of regulatory proteins that function in an NAD+-dependent manner. The mammalian family of sirtuins is composed of seven histone deacetylase and ADP-ribosyltransferase proteins (SIRT1-SIRT7) that are found throughout the different cellular compartments of the cell. Sirtuins in the brain have received considerable attention in cognition due to their role in a plethora of metabolic and age-related diseases and their ability to induce neuroprotection. More recently, sirtuins have been shown to play a role in normal physiological cognitive function, and aberrant sirtuin function is seen in pathological cellular states. Sirtuins are believed to play a role in cognition through enhancing synaptic plasticity, influencing epigenetic regulation, and playing key roles in molecular pathways involved with oxidative stress affecting mitochondrial function. This review aims to discuss recent advances in the understanding of the role of mammalian sirtuins in cognitive function and the therapeutic potential of targeting sirtuins to ameliorate cognitive deficits in neurological disorders.